My-Wakaf: a waqf of property management application / Razin Azri Mohamad Razid ...[et al.] - Mohamad Razid, Razin Azri; Ibrahim, Alif Faisal; Jamaluddin, Muhammad Nabil Fikri; JM Gining, Ray Adderley (UiTM Cawangan Perlis, 2021)
In almost every Islamic country, the number of waqf properties is increasing at an exponential rate. As a result, managing such abundant amount of waqf properties can be very tedious and challenging. In Malaysia, waqf properties is managed by respective State Islamic Religious Council and are still using traditional method of recording all waqf asset. As a result, the My-Wakaf prototype mobile application was created to aid with the workload of managing waqf assets or properties. The methodology used for the project is the Waterfall model that is based on the original System Development Life Cycle (SDLC) that have 5 phases which are Planning, Design, Development, Testing and Documentation phase. My-Wakaf application is developed using Android Studio and it is integrated with Firebase Cloud database to help store waqf assets information securely to be accessed anywhere, reducing the human errors and cost of managing such properties. According to a user acceptability test conducted on numerous responders, the majority of them were highly happy with the My-Wakaf application's general functionality. Finally, it is intended that My-Wakaf would help the Muslim community as a whole by increasing awareness of waqf knowledge and stimulating economic growth.